Perpustakaan Sebagai Penunjang Penelitian Di Balai Arkeologi Jawa Barat - Azhar Rachman (JURNAL PANALUNGTIK, 2020)
Balai Arkeologi Jawa Barat has a thematic library that has a collection of books on archeology and other sciences that support archeological research. This library has a collection of books totaling nearly 2000 titles. Besides books, there are also other collections, namely CDs and leafts. This library does not only serve researchers but also people who need archeology-themed books. Researchers at Balai Arkeologi Jawa Barat each year carry out research activities, this of course requires library resources and to facilitate researchers in searching for books also requires easy access and availability of books. The purpose of this study is to see whether the West Java Archaeological Center Library can support researchers in the West Java Archaeological Center in their research. The research method used was direct observation and distributing questionnaires to researchers at the Archeology Center of West Java. The research results of this collection of the library books of the West Java Archaeological Center are quite complete, relevant and quite up to date as data information and references to support research activities.